Integrasi Konsep Hadhanah dan Asuhan Kebidanan Pra Sekolah: Studi Kasus Anak Pra Sekolah Yang Diasuh di Tempat Kerja - Yumarni, Fazira; Ningsih, Fitriani; Harta, Harta; Aisyah, Aisyah; Nurina, Siti (Sharia Journal and Education Center Publishing, 2025)
Early childhood care plays a vital role in their development, especially during the preschool years, which are critical for physical, cognitive, and social growth. This article examines the integration of hadhanah (Islamic parenting principles) and midwifery care for preschool-aged children being cared for at their parents' workplaces. The study utilized a qualitative case study method, involving children, caregivers, and healthcare professionals in daycare centers. Results indicate that integrated care enhances various aspects of child development, including language skills, social development, and physical health. The study also identifies challenges and implementation strategies, emphasizing collaboration among parents, caregivers, and medical professionals. This care model has proven to increase parental satisfaction and positively impact children's well-being.